THE CAPITAL STRUCTURE OF MANUFACTURING INDUSTRIES IN INDIA - K. DEEPIKA,; B. MATHAVAN, (The Bioscan, 2025)
This study examines the growth performance of the capital structure of Indian manufacturing industries over the period from 1981–82 to 2019–20, using secondary data sourced from the Annual Survey of Industries (ASI). The analysis covers the key principal characteristics, namely number of factories, fixed capital, working capital, invested capital, and depreciation, deflated to constant prices with 2011–12 base year. Methodologically, the study employs the semi-logarithmic in that log-quadratic trend models is obtained to estimate the overall growth trends, as well as a two-kink exponential model to capture the sub-period growth rates across the period of pre-reform (1981–82 to 1990–91), post-reform (1991–92 to 2000–01), and transformation (2001–02 to 2019–20) phases. The findings reveal that the pre-reform period was marked by negative and decelerated growth rate, reflecting regulatory rigidities and limited access to capital. However, the post-1991 liberalization reforms catalysed accelerated growth rate across all the capital structure indicators, with particularly sharp increases in fixed capital, invested capital, and depreciation in the transformation phase. Overall, the results highlight the sector’s transition from a period of sluggish and uneven growth to accelerated capital accumulation and financial strengthening in the post-reform era. The study underscores how liberalization policies improved access to finance and structural reforms significantly influenced the composition and growth of capital structure, thereby enhancing the long-term growth potential and sustainability of India’s manufacturing industries.